(untitled) (Cardiovascular Journal, 2021)
Background: coronary artery bypass surgery (CABG) is expensive, uses disposable appliances and patients require more perioperative intensive care, long stay in hospital and often have a lengthy recovery time. These complications, together with the growing trend towards less invasive techniques in other areas of surgery, have encouraged cardiac surgeons to see if minimally invasive cardiac surgery can become a reality with improved outcomes and costs. Methods: This is a prospective nonrandomized comparative clinical study done at the Department of Cardiac Surgery in National Institute of Cardiovascular Diseases (NICVD) Sher-E- Bangla Nagar, Dhaka from July 2006 to June 2008 among routine CABG patients. Purposive sampling was done with 26 patients in group A selected for MIDCAB and 24 patients in Group B selected for conventional CABG surgery. Patients were followed up for three months. Postoperative outcomes were assessed to evaluate the safety and efficacy of MIDCAB in relation to conventional CABG. Results: Mean age were 54.19 vs 53.87 in group A and Group B. 92.3% vs 87.5% were male respectively. Mean duration of operation, per operative blood loss transfusion and arrythmia were lower in MIDCAB group (p<0.05) number of grafts were also statistically significant (p< 0.001). Regarding post-operative outcome ventilation time in hours ICU stay post-operative hospital stay in days, postoperative MI and stroke rate were lower in favor of group A MIDCAB patients (p<0.001). Three months postoperatively six-meter walking distance is also statistically significant in favor of Group A MIDCAB (p<0.01) patients. However, pain score in early post-operative period was higher in group A significantly but it decreased significantly in late post-operative period which is also highly statistically different (p<0.001). However, mortality and quality of life at three months were similar in both groups. Conclusion: No difference in mortality rates detected between MIDCAB and CCABG group. But there was evidence that MIDCAB is associated with less perioperative and early postoperative morbidity and improved quality of life. The MIDCAB surgery is an effective procedure of complete revascularization in ischemic heart diseases like CCABG. The procedure is associated with shorter operating time, shorter ICU stay time, shorter hospital stays and better quality of life than for CCABG. Cardiovasc. j. 2021; 13(2): 135-143